Perceptions on the contributions of Service-Learning in Physical Education: an autobiographical perspective from university teachers cross-narratives - Marc Franco-Sola; Sara Figueras Comas; Josep Campos-Rius; Enric Maria Sebastiani Obrador (Universidad de La Rioja, 2021)
This research aims to understand the perceptions of university teachers in the field of Physical Education and the implementation of Service-Learning (SL) methodology in their classes. The research focuses on: a) Interpreting the beliefs that teachers attribute to the contributions of the methodology in their own professional teaching career; b) Understanding their perception in relation to the evolution of the students learning through their experiences during these years. To develop the research, the biographical method is been used and the data is been collected through the crossed-life-stories of 4 teachers from the Physical Activity and Sports Sciences degree and Primary Education degree. Professors accredited more than five years of experience in the implementation of Service-Learning methodology in their Physical Education classes. The results of the qualitative analysis reveal the value of the meanings attributed to a methodology that increase the competency learning in Blanquerna Faculty of Psychology, Educational Sciences and Sports (Ramon Llull University).